O DESENVOLVIMENTO NEUROPSICOMOTOR DOS 2 AOS 8 MESES DE IDADE DE CRIANÇAS NASCIDAS PREMATURAS - Bonamigo, Elenita C. B.; Sacon, Alana B.; Llano, Débora C.; Pretto, Luciana M.; Souto, Cristiane S.; Winkelmann, Eliane R. (Salão do Conhecimento, 2013)
Resumo